Who Opposes Immigrants' Integration into the Labor Market? The Swiss Case - Tobias Müller; Silvio H. T. Tai (Swiss Journal of Economics and Statistics, 2010)
First, we spell out a political-economy model, based on segmented labor markets, which explains why a guest-worker system is preferred to a non-discriminatory immigration regime and why measures to improve the integration of low-skill immigrants tend to be opposed subsequently. The model also predicts that attitudes towards the integration of immigrants are positively related to education. Second, we examine the empirical evidence on attitudes towards the integration of immigrants. Our findings from Swiss data are consistent with the prediction of the theoretical model. Both economic and non-economic factors seem to matter in the positive relationship between attitudes and education.
Keywords: F22; J61; D72; 330; immigration; immigrant integration; guest-workers; political economy